2016
DOI: 10.1130/g38254.1
|View full text |Cite
|
Sign up to set email alerts
|

Aridity-induced Miocene canyon incision in the Central Andes

Abstract: The relationship between the rise of the Andean mountain chain and the onset of aridity on its western margin is poorly understood. Canyon incision on both the eastern and western flanks of the chain is interpreted generally as a direct response to increased rock uplift, but may equally have been the result of climate change. Here we record some of the oldest canyon incision on the western Andean margin by tracking the downward migration of the local water table using (U-Th)/He hematite geochronology on vertic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 26 publications
2
48
0
Order By: Relevance
“…First, local (catchment‐scale) tectonic effects are evident from our factor analysis that indicates a strong linear correlation and covariation of denudation rate and mean channel steepness index. In northern Chile, previous studies have suggested that river knickpoints and channel steepness indices are indicative of relative surface uplift (Cooper et al, ; Hoke et al, ). Although denudation rates in this study cannot be related to absolute uplift rates of the Central Andes (Regard et al, ), the spatial distribution of denudation rates and channel steepness indices are most likely related to local, faulting‐controlled, tectonic or earthquake‐induced landslide activity where the highest denudation rates at 19°S and 21°S are observed.…”
Section: Discussionmentioning
confidence: 99%
“…First, local (catchment‐scale) tectonic effects are evident from our factor analysis that indicates a strong linear correlation and covariation of denudation rate and mean channel steepness index. In northern Chile, previous studies have suggested that river knickpoints and channel steepness indices are indicative of relative surface uplift (Cooper et al, ; Hoke et al, ). Although denudation rates in this study cannot be related to absolute uplift rates of the Central Andes (Regard et al, ), the spatial distribution of denudation rates and channel steepness indices are most likely related to local, faulting‐controlled, tectonic or earthquake‐induced landslide activity where the highest denudation rates at 19°S and 21°S are observed.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing upstream channel steepness patterns in fluvial landscapes have been attributed to an increase in rock uplift rate in other mountain ranges (Wobus et al, 2003). Gradually increasing patterns of rock uplift like those shown in Figure 3 do create upstream increases in channel steepness, however, this effect does not create discrete concave knickpoints (Kirby and Whipple, 2001;Cooper et al, 2016) like those seen in the Olympics. Neither concave nor convex knickpoints are co-linear in map view as might be expected if they were fault controlled (Figure 2 and S3).…”
Section: Discussionmentioning
confidence: 99%
“…In a long‐standing arid setting, tectonic forcings would not be well recorded in a slow‐to‐respond exhumational signal. Furthermore, documented knickpoints in the river profiles of the northern Chilean fore arc are an indicator of transient topography (e.g., Cooper et al, 2016; Hoke et al, 2007). Vertical fault motion could imprint local changes in exhumation and has been demonstrated to be the case in southern Peru (Noury et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While directly equating cooling rates with erosion and uplift may be specious, with thoughtful sampling and consideration of thermal properties in a kinematic model, mineral cooling ages can track, to a first order, the rates of rock exhumation and thus the erosion history of a region. Previous thermochronometric studies quantifying exhumation in the Central Andean fore arc have often focused on canyon incision rates as proxies for timing of surface uplift (Cooper et al, 2016; Hoke et al, 2007; Schildgen et al, 2007; Schildgen et al, 2009). Rapid and sustained river incisions have been suggested as mechanisms for inciting tectonic deformation.…”
Section: Introductionmentioning
confidence: 99%